ANALYZING THE ROLE OF THE UNITED NATIONS IN FACING TALIBAN RESTRICTION WOMEN’S EDUCATION IN AFGHANISTAN 2021 - Azzahrah, Adilia Khansa; Yumitro, Gonda (Indonesian Association for International Relations, 2025)
The purpose of this research is to analyze the role of the UN in addressing the restrictions on women's education imposed by the Taliban government in 2021. This study employs a qualitative approach with a literature review methodology. Primary data consists of research findings from journals accessed through databases like Scopus, Publish or Perish 8, Google Scholar, and Google, using keywords such as Afghanistan, Discrimination, UN, Education, and Restrictions, with a timeframe limit from 2019 to 2024. Secondary data includes various relevant literature. The collected data is then analyzed using a Human Rights perspective. The author finds that the UN has played a role in addressing ongoing issues in Afghanistan and in efforts to prevent further problems, through advocacy activities, technical assistance, and humanitarian support. Additionally, the UN engages the international community to exert pressure on the Taliban government and to facilitate dialogue with them